Development of a software package with GUI for the evaluation of monolithicity factors of RC jacketed columns. (February 2023) - Minafò, Giovanni; Camarda, Gaetano
Abstract: The design of reinforced concrete (RC) jacketing for retrofitting substandard columns is a common practice when approaching the structural rehabilitation design of existing structures. In this framework, international technical codes suggest to assume the hypothesis of monolithic section and finally affecting the deduced performances by some empirical factors, known in the literature as monolithicity factors. The assessment of these coefficients is a difficult task, and only some rough assumptions can be found in the modern codes. This paper presents the development of a software package able to perform the static non-linear analysis of RC jacketed columns and evaluating the actual value of the monolithicity factor. The code is developed in an integrated environment, taking advantage of finite element (FE) framework OpenSees and adopting Matlab for developing an user-friendly Graphical User Interface (GUI). The fibre-section approach is automatically implemented for modelling the flexural behaviour of the column and the effective bond between the old and new column in considered through a distribution of non-linear springs. Finally, the parametric analysis performed by the proposed tool allows to present the monolithicity factors as a function of the key parameters. Highlights: A modelling approach is exploited to simulate the behaviour of RC jacketed columns. The OpenSees environment is adopted for fibre-section modelling. The model is integrated in a toolkit with an user-friendly graphical user interface. The developed package allows the evaluation of monolithicity factors.